THE ANALYSIS OF DEPENDENCE OF NUMBER OF CELLULAR NETWORKS SUBSCRIBERS FROM THE POPULATION INCOME - Конахович, Г.; Козлюк, І.; Одарченко, Р.; Ткаченко, В. (Science-based technologies, 2012)
A study on implementation technology LTE in the world and in Ukraine in particular is given. The method of forecasting demand for advanced telecommunications systems, and predicted possible number of LTE network users in Ukraine are given. Forecast is based on correlation and regression analysis and takes into account statistics of the number of GSM users in previous years. Method allows to determine the demand for LTE network resources, based on the age structure of potential users and their income.